A cascade FRET photosensitizer that enhances photodynamic therapy for ocular melanoma. (December 2022) - Ruan, Jing; Li, Fang; Tian, Hao; Yu, Jie; Deng, Hongpei; Ge, Shengfang; Leong, Kam W.
Abstract: Photodynamic therapy (PDT) relies on the generation of cytotoxic singlet oxygen ( 1 O2 ) from an otherwise nontoxic photosensitizer accumulated in tumor tissue to treat cancer. However, PDT of uveal melanoma, the most common adult intraocular cancer, using potent porphyrin derivatives as photosensitizers has shown limited therapeutic efficacy due to low bioavailability and 1 O2 yield. Here, considering the uveal melanoma microenvironment of endogenous melanin, which has a high absorption between 300 nm and 500 nm, we design a carbon dot-based photosensitizer that uses multiple different pathways to generate 1 O2 . We conjugated gadolinium (Gd)-doped carbon dots (Gd@Cdots) with the porphyrin-derivatives chlorin e6 (Ce6) and verteporfin (Ver). The resulting nanoparticle (Gd@Cdots/Ce6/Ver) generates 1 O2 under UV irradiation mainly in cascade FRET from Gd@Cdots to Ce6 and then to Ver; the photoactivated Ver, in turn, transfers its energy to 3 O2 to generate 1 O2 . In human uveal melanoma MUM-2B cells in vitro, Gd@Cdots/Ce6/Ver generated 7.1- and 2.4-fold higher production of hydroxyl radical (·OH) and superoxide anions (O2 - ·) following UV irradiation than Gd@Cdots, indicating greater induction of tumor cell apoptosis. In an orthotopic mouse model of uveal melanoma, PDT with Gd@Cdots/Ce6/Ver showed the same trend of superior potency in tumor growth inhibition. This photosensitizer design improves the PDT efficacy of uveal melanoma by enhancing the production of 1 O2 and should be of broad utility to other PDT. Graphical Abstract: ga1 Highlights: A cascade FRET photosensitizer for photodynamic therapy of ocular melanoma is developed. The cascaded photosensitizer has highly coincident absorption light range with melanin which is highly expressed in ocular melanoma. The cascaded FRET photosensitizer yield 1 O2 and ROS via multiple photoactivation pathways. The cascaded photosensitizer shows superior potency in tumor growth inhibition and little side effect on normal tissues.